Effects of urbanization on taxonomic, functional and phylogenetic avian diversity in Europe - Morelli, Federico; Benedetti, Yanina; Ibáñez-Álamo, Juan Diego; Tryjanowski, Piotr; Jokimäki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa; Suhonen, Jukka; Díaz, Mario; Møller, Anders Pape; Moravec, David; Prosek, Jiri; Bussière, Raphaël; et al. (The Science of the total environment, 2021)
Europe is an urbanized continent characterized by a long history of human-wildlife interactions. This study aimed to assess the effects of specific elements of urbanization and urban pollution on complementary avian diversity metrics, to provide new insights on the conservation of urban birds. Our study recorded 133 bird species at 1624 point counts uniformly distributed in seventeen different European cities. Our results thus covered a large spatial scale, confirming both effects of geographical and local attributes of the cities on avian diversity. However, we found contrasting effects for the different diversity components analyzed. Overall, taxonomic diversity (bird species richness), phylogenetic diversity and relatedness were significantly and negatively associated with latitude, while functional dispersion of communities showed no association whatsoever. At the local level (within the city), we found that urban greenery (grass, bush, and trees) is positively correlated with the number of breeding bird species, while the building cover showed a detrimental effect. Functional dispersion was the less affected diversity metric, while grass and trees and water (rivers or urban streams) positively affected the phylogenetic diversity of avian communities. Finally, the phylogenetic relatedness of species increased with all the main indicators of urbanization (building surface, floors, pedestrian's density and level of light pollution) and was only mitigated by the presence of bushes. We argue that maintaining adequate levels of avian diversity within the urban settlements can help to increase the potential resilience of urban ecosystems exposed to the stress provoked by rapid and continuous changes. We listed some characteristics of the cities providing positive and negative effects on each facet of urban avian diversity.
Keywords: ptáci; Humans; Urbanization; Birds; Noise pollution; Phylogeny; Conservation; Ecosystem; Functional diversity; Light pollution; lidé; zvířata; Europe; Cities; Biotic homogenization; Urban green; biodiverzita; fylogeneze; urbanizace; Bird diversity; Animals; šlechtění rostlin; velkoměsta; Plant Breeding; Evropa; ekosystém; Biodiversity